From Jamaica to the Cape Flets : reflecting on the manifestations of a Cape Hip Hop culture, 1983-2015 - Van Wyk, Adrian (Stellenbosh : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.